HALAL FOOD PRODUCTS LABELING ACCORDING TO ISLAMIC BUSINESS ETHICS AND CONSUMERS PROTECTION LAW - Iyut Rizqi Utami (AL- IKTISAB Journal of Islamic Economic Law, 2018)
Halal food products labeling is a form of producer responsibility and fulfilling protectionist authority of Muslim consumers and a form of ethics in the business world. From some of the cases that coming explain a lot of manufacturers do not take full responsibility for protecting Muslims consumers authority. The purpose of this study is to know how the role of Halal food products labeling according Islamic business ethics and consumer protection law. The results of this study concluded that labeling of Halal on food products have goals and values, the values that will concrete the good behavior of an ethical business, noble and professionals in the business which pay attention to spiritual values and social interests so that will protect consumers. Halal labeling is a form of legal guarantees that will protect consumers in way of physical and spiritual, it is mean protecting consumers with regard to physical health and observance of Muslims in carrying out the commands of Allah. In addition, the labeling of Halal became absolute thing to do and obeyed, because rules are specified in Act No. 8 of 1999 on Consumer Protection and Law No. 33 of 2014 concerning the guarantee of halal products.Key Words: Halal Label, Islamic Business Ethics and Consumer Protection Laws